(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Adjustment is a behavioural process of balancing conflicting needs against obstacles within the environment. Psychological issues arise while there is incapacity to make normal modifications to a fundamental task. Stress is the most common mental problem in Divyang individuals. Physically handicapped person encounter issues when they are attempting to adjust the demands of residing in a social environment. Their problems aren’t handiest due to their disability, but additionally to alter to a world that adopts a callous or antagonistic mind-set toward them that exacerbates their issues and endangers their lifestyles as human beings.